2019
DOI: 10.2147/ott.s220383
|View full text |Cite
|
Sign up to set email alerts
|

<p>Association Of Initial Epidermal Growth Factor Receptor Tyrosine Kinase Inhibitors Treatment And EGFR Exon 19 Deletion With Frequency Of The T790M Mutation In Non-Small Cell Lung Cancer Patients After Resistance To First-Line Epidermal Growth Factor Receptor Tyrosine Kinase Inhibitors</p>

Abstract: BackgroundThe present study analyzed the relationship between clinical features and the T790M mutation in non-small cell lung cancer (NSCLC) patients resistant to epidermal growth factor receptor tyrosine kinase inhibitors (EGFR-TKIs) treatment.MethodsNSCLC patients with resistance to first-generation EGFR-TKIs in which the disease control time was more than 6 months after initial TKI treatment were enrolled. T790M mutation analysis was performed using one of the following methods according to each manufacture… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 32 publications
2
2
0
Order By: Relevance
“…In our study, the accumulated prevalence of the T790M QTc prolongation 0 (0) 0 (0) 0 0 mutation was 60% (66/110), which was higher than that previously reported in other studies (36.4%-54.3%). [11][12][13] This finding is consistent with those of previous reports showing that repeated biopsy might lead to this higher incidence of T790M mutation. 14,15 A prospective observational registry study showed that among 34 patients who confirmed T790M-negative on the first rebiopsy, 20 patients went through repeat rebiopsy following interval therapy, and showing that 7 (35%) patients detected T790M-positive mutation 16 ; Ichihara et al reported that among 30 patients diagnosed as T790M-negative when underwent the first rebiopsy, 21 patients underwent repeat rebiopsy after interval treatment, then 12 extra patients were detected T790Mpositive (12/21, 57.1%).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In our study, the accumulated prevalence of the T790M QTc prolongation 0 (0) 0 (0) 0 0 mutation was 60% (66/110), which was higher than that previously reported in other studies (36.4%-54.3%). [11][12][13] This finding is consistent with those of previous reports showing that repeated biopsy might lead to this higher incidence of T790M mutation. 14,15 A prospective observational registry study showed that among 34 patients who confirmed T790M-negative on the first rebiopsy, 20 patients went through repeat rebiopsy following interval therapy, and showing that 7 (35%) patients detected T790M-positive mutation 16 ; Ichihara et al reported that among 30 patients diagnosed as T790M-negative when underwent the first rebiopsy, 21 patients underwent repeat rebiopsy after interval treatment, then 12 extra patients were detected T790Mpositive (12/21, 57.1%).…”
Section: Discussionsupporting
confidence: 92%
“…This study showed the importance of repeated rebiopsy. In our study, the accumulated prevalence of the T790M mutation was 60% (66/110), which was higher than that previously reported in other studies (36.4%–54.3%) 11–13 . This finding is consistent with those of previous reports showing that repeated biopsy might lead to this higher incidence of T790M mutation 14,15 .…”
Section: Discussionsupporting
confidence: 89%
“…Although patients with NSCLC harboring EGFR mutations may achieve prolonged survival and a preserved QoL, resistance invariably develops. The T790M mutation is mainly responsible for acquired drug resistance (66,69,70). In the ALTER0303 trial, 18 patients with T790M benefited from anlotinib compared with placebo, with a median OS of 21.5 and 6.6 months, respectively (71).…”
Section: Clinical Trials Of Anlotinibmentioning
confidence: 99%
“…Mutations in EGFR are known to impact the outcome of anti-EGFR therapies in LC [151,152]. Exon 19 deletion and L858R can predict the sensitivity to treatment using erlotinib and gefitinib, whereas the T790M mutation of exon 20 is associated with acquired resistance to these drugs [153][154][155]. With the FDA approval of osimertinib, a thirdgeneration EGFR inhibitor which is now the standard front-line therapy for EGFR-mutant NSCLC, a noninvasive tool to detect secondary EGFR mutations has become imperative.…”
Section: Egfr Expression On Ctcsmentioning
confidence: 99%